2019
DOI: 10.1186/s12939-019-1035-x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to diabetes self-management for adults with type 2 diabetes in low-resource settings in Mexico City: a qualitative descriptive study

Abstract: Background The prevalence of type 2 diabetes (T2D) in Mexico is one of the highest in the world, with high morbidity and mortality, and difficulty meeting glycemic targets. The purpose of this study was to identify the challenges for T2D self-management as perceived by both adults with T2D and health care providers in primary health clinics from Seguro Popular in Mexico City. Methods This was a qualitative descriptive study conducted in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 40 publications
5
44
1
4
Order By: Relevance
“…In the domain “reinforcement” (15 studies) [ 27 , 28 , 31 , 33 , 37 , 39 , 41 , 44 , 50 , 52 , 53 , 59 , 61 , 62 , 77 , 78 , 80 , 84 , 85 ], the lack of symptoms and the side effects of medication were seen as factors that could result in people with diabetes stopping the treatment (12 studies).…”
Section: Resultsmentioning
confidence: 99%
“…In the domain “reinforcement” (15 studies) [ 27 , 28 , 31 , 33 , 37 , 39 , 41 , 44 , 50 , 52 , 53 , 59 , 61 , 62 , 77 , 78 , 80 , 84 , 85 ], the lack of symptoms and the side effects of medication were seen as factors that could result in people with diabetes stopping the treatment (12 studies).…”
Section: Resultsmentioning
confidence: 99%
“…Studies included in our review consistently reported an increased prevalence of diabetes with age. Diabetes care challenges specific to this age group include risk of obesity or undernutrition [ 42 , 56 ], increased risk for disability [ 57 ], economic barriers to appropriate access to health care [ 42 ], disruption in funding of health insurance [ 275 ], disparate completion of diabetes care guidelines based on health insurance coverage [ 276 ], inequalities in access to and utilization of health care services [ 277 279 ], complex medical care needs and frailty [ 280 ], cultural beliefs, mental health, and lack of family or social support [ 281 ], among others. Prevention of diabetes and its complications and reliable continuity of care and social support [ 282 ] need to be especially tailored for this population across the region.…”
Section: Additional Observationsmentioning
confidence: 99%
“…We also explored how the cultural context, family, and health system shape beliefs and practices, and deliver or support care related to T2D. This qualitative study has been published [25]; in the following section, we summarize the main points that informed our intervention development.…”
Section: Methods and Resultsmentioning
confidence: 99%